Current and future aspects of IBD research and treatment: The 2022 perspective - Stange, Eduard F. (Frontiers in Gastroenterology, 2022)
Inflammatory bowel diseases (IBD) have seen major progress in current concepts and treatment regimes. Based on the theory of an inadequate “overshoot” mucosal immune response to the intestinal microbiome, therapies have been developed to interfere with the key mediators of inflammation from cytokines including TNF and IL12/23, to integrins like 4ß7 and intracellular cytokine signal transducers like janus kinases. Recently, sphingosine-1-receptor agonists were marketed to suppress mucosal inflammation by sequestering lymphocytes in peripheral lymph nodes. However, the aim of these regimes targeting immunity to induce a long-term deep remission including mucosal healing is missed in most patients. Contrasting these anti-inflammatory mechanisms of action, the pathogenic focus has finally shifted to the mucosal antibacterial barrier, both in Crohn´s disease and ulcerative colitis. Translating this novel concept requires a completely different approach but, in the end, may come closer to a cure of these devastating diseases, where an incomplete immune modulation fails to achieve the key endpoints: halting disease activity and progression. This review aims to give an overview of past, current and future concepts in IBD focusing on both pathogenesis and consequent therapy. A cure is in sight only if both reflect the actual key mechanisms of slow bacterial entry into the mucosa, are harmonized and in line.